Calcitonin gene-related peptide levels in tear fluid are elevated in migraine patients compared to healthy controls. (October 2019) - Kamm, Katharina; Straube, Andreas; Ruscheweyh, Ruth
Background: Calcitonin gene-related peptide (CGRP) released from trigeminal nerve fibres indicates trigeminal activation and has a key role in migraine pathophysiology. The trigeminal nerve directly innervates the eye. Therefore, in this study, we compared Calcitonin gene-related peptide in tear fluid of migraine patients and healthy controls. Methods: Calcitonin gene-related peptide concentrations in tear fluid and plasma of 48 episodic and 45 chronic migraine patients and 48 controls were assessed using ELISA. Results: Calcitonin gene-related peptide levels in tear fluid (0.94 ± 1.11 ng/ml) were ∼140 times higher than plasma concentrations (6.81 ± 4.12 pg/ml). Tear fluid CGRP concentrations were elevated in interictal migraine patients (1.10 ± 1.27 ng/ml, n = 49) compared to controls (0.75 ± 0.80 ng/ml, p  = 0.022). There was no difference in tear fluid CGRP levels between interictal episodic and chronic migraine patients (episodic: 1.09 ± 1.47 ng/ml, n = 30 and chronic: 1.10 ± 0.89 ng/ml, n = 19) and no correlation of tear fluid CGRP levels with headache frequency in interictal patients (rho = 0.062, p  = 0.674). Unmedicated ictal migraine patients had even more elevated tear fluid CGRP levels than interictal migraine patients (1.92 ± 1.84 ng/ml, n = 13, p  = 0.102), while medicated ictal migraine patients had lower levels (0.56 ± 0.47 ng/ml, n = 25, p  = 0.011 compared to interictal patients), which were undistinguishable from controls ( p  = 0.609). In contrast to tear fluid, no significant group differences were found in plasma CGRP levels. Conclusion: To the best of our knowledge, this study shows, for the first time, increased CGRP tear fluid levels in migraine patients compared to healthy subjects. Detection of calcitonin gene-related peptide in tear fluid is non-invasive, and likely allows a more direct access to CGRP released from the trigeminal nerve than plasma sampling.